ANALYSIS OF CONFLICT AND INTRINSIC ELEMENTS IN THE SHORT STORY ENTITLED “NARA DILEMA” BY ALYA KHALISAH IN STUDY OF LITERARY SOCIOLOGY - Aurin, Nasyah; Kabeakan, Nuraini; Nasution, Anggi Dwi Rosidi; Srimiati, Srimiati; Natasya, Rika (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
This study aims to investigate social conflict from the short story titled